INOVASI MINUMAN SEHAT: DEMONSTRASI PEMBUATAN SIRUP SUNGKAI DI NAGARI SIPINANG, KECAMATAN PALEMBAYAN KABUPATEN AGAM - Dillasamola, Dwisari; Nasif, Hansen; Alen, Yohannes; Aldi, Yufri; Syofyan, Syofyan; Sayyida, Alya (LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) Universitas Andalas, 2024)
The Sungkai plant (Peronema canescens Jack.) is known for its various health benefits, particularly as a natural immunostimulant. In West Sumatra, this plant is abundant and widely used in traditional medicine. This activity aimed to provide education and a demonstration to the community on how to process Sungkai leaves into a healthy syrup, thereby increasing the use of this plant as a daily health drink. The event was conducted through a live demonstration in Kanagarian Sipinang, Palembayan District, Agam Regency. The process of making Sungkai syrup involved several stages, starting from selecting the leaves, boiling them, and mixing them with other ingredients such as sugar and/or lemon juice to enhance the flavor. The results of this activity showed high enthusiasm among participants, with a total of 40 attendees. Before the demonstration, data from questionnaires revealed that 80% of respondents had heard about Sungkai syrup. During the demonstration, most participants expressed great interest in the syrup-making process, particularly in the aspect of processing Sungkai leaves into an extract that can be used as a base for syrup. This demonstration successfully enhanced participants' knowledge and skills in utilizing Sungkai leaves as a healthy drink. With further education and support, Sungkai syrup has great potential to be developed as a flagship product that supports both public health.